1996
DOI: 10.1051/aas:1996102
|View full text |Cite
|
Sign up to set email alerts
|

uvby-β photometry of high-velocity and metal-poor star. VIII. Stars of very low metal abundance

Abstract: A catalogue of uvby-β photometry for 87 of the turn-off and subgiant stars from the HK survey of Beers et al. (1992) is given. Most of these stars have [Fe/H]≤ −2.5. These photometric data have been taken and reduced using the same techniques as in our previous two uvby-β catalogues. An error analysis has been made; typical mean observational errors for a star with V = 14. m 2 are 0.008, 0.007, 0.011, 0.010 and 0.012 in V , (b − y), m1, c1 and β, respectively. Our photometric data are also compared to the UBV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 23 publications
(43 reference statements)
6
39
0
1
Order By: Relevance
“…There is a mean difference of 4 Gyr in the absolute age due to diffusion, as proposed by Salaris & Weiss (2001). The results obtained for ages from the nodiff-isochrones agree better with those of Unavane et al (1996) and Schuster et al (1996).…”
Section: Age Reduction Due To Atomic Diffusionsupporting
confidence: 63%
See 2 more Smart Citations
“…There is a mean difference of 4 Gyr in the absolute age due to diffusion, as proposed by Salaris & Weiss (2001). The results obtained for ages from the nodiff-isochrones agree better with those of Unavane et al (1996) and Schuster et al (1996).…”
Section: Age Reduction Due To Atomic Diffusionsupporting
confidence: 63%
“…We could see that the results obtained using BaSTI models agreed better with those obtained from the nodiff-isochrones, while Y 2 results agreed better with those obtained from diff-isochrones. In this way, we could explain why the previous ages obtained with this method (Unavane et al 1996;Schuster et al 1996) are greater than our own. Given the current debate about the efficiency with which atomic diffusion acts in stellar interiors, our results show a strong argument against fully inhibited diffusion in metal-poor halo stars.…”
Section: Summary and Concluding Remarksmentioning
confidence: 64%
See 1 more Smart Citation
“…The uvby-β data presented here in Table 1 for the solar twins were taken using the H. L. Johnson 1.5 m telescope at the San Pedro Mártir Observatory, Baja California, México (hereafter SPM), and the same six-channel uvby-β photoelectric photometer as for the northern observations of Schuster & Nissen (1988, hereafter SN), for all the uvby-β observations of Schuster et al (1993, hereafter SPC), the northern data of very-metalpoor stars by Schuster et al (1996), the uvby-β data for verymetal-poor stars in Table 1 of Schuster et al (2004), and the uvby-β data for high-velocity and metal-poor stars in Table 1 of Schuster et al (2006). The new uvby-β values for solar twins included here in Table 1 were taken during three observing runs in November 2007 (8 nights), April 2008 (7 nights), and September 2008 (4 nights).…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…The age scatter in halo field stars is at least as great as that in the young halo cluster system (Schuster et al 1996), and perhaps greater -as shown by the apparently young, blue metal poor stars of Preston et al (1994) and the carbon stars of Totten & Irwin (1996), both of which are attributed to satellite accretion. Evidence for significant phase space complexity, manifested as "moving groups", streams, or other kinematic substructure of halo stars (Carney et al 1996, Majewski et al 1996a, summary in Majewski et al, 1996b) is consistent with a dynamically unrelaxed, accreted outer halo.…”
Section: Accretion In the Halomentioning
confidence: 91%